Physical, chemical, and biological characteristics of crab (Scylla spp.) from East Kalimantan, Indonesia - FANGGI FANGGI; ESTI HANDAYANI HARDI; ANDI NIKHLANI; ANTON PANJI MAHENDRA; NOVITA NOVITA; FITRI NOERHIDAYANTI (Society for Indonesian Biodiversity, 2023)
Abstract. Fanggi, Hardi EH, Nikhlani A, Mahendra AP, Tarbiyah, Novita, Noerhidayanti F. 2023. Physical, chemical, and biological characteristics of crab (Scylla spp.) from East Kalimantan, Indonesia. Biodiversitas 24: 4998-5006. Mud crab (Scylla spp.) is a direct export commodity to China from East Kalimantan, Indonesia. The majority of crabs are caught wild by traditional farmers in some districts. Early detection of crab quality is required to prevent the rejection of mud crab export products due to size, heavy metals, and infections. Fifteen samples from 15 farms in Balikpapan, Indonesia, were evaluated for physical parameters (weight, carapace width, sex, completeness of morphology, and identification of species), chemical parameters (Cu, Pb, Mg, Cd, and As), and biological parameters for the detection of White Spot Syndrome Virus (WSSV). The crab catches are from Kutai Kartanegara, Paser, and Penajam Paser Utara Districts. The physical examination of the crabs revealed a weight of 441.73±88.14 g, a carapace width of 11.92±0,59 cm, sexes of 14 males and 1 female, species including Scylla serrata (Forskål, 1775), Scylla olivacea (Herbst, 1796), Scylla paramamosain (Estampador, 1950), and Scylla tranquebarica (Fabricius, 1798), and 93.3% of the crabs had morphological completeness. The chemical examination of heavy metals, including Cu, Pb, Mg, Cd, and As, is still limited to fish products, while Fe has passed the quality standard, and WSSV has infected no crabs. The investigation found that 40% of East Kalimantan Province crab exports did not meet carapace width criteria. No WSSV pathogen was found in the samples. However, crab meat Fe concentration exceeded requirements.